Back row l.t.r. Jong, Jonassen, Kraschutzki, Salmon, Morris, Dautry. Front row l.t.r. Penrose, (?) Bing, Tatum, Day
Back row l.t.r. Jong, Jonassen, Kraschutzki, Salmon, Morris, Dautry. Front row l.t.r. Penrose, (?) Bing, Tatum, Day.